Phylogeography of Himalrandia lichiangensis from the dry-hot valleys in Southwest China - Qiao, Yaomei; Liu, Jian; Gong, Xun (Frontiers in Plant Science, 2022)
Both changing tectonics and climate may shape the phylogeographic patterns of plant species. The dry-hot valleys in southwestern China harbor a high number of endemic plants. In this study, we investigated the evolutionary history and potential distribution of an endemic shrub Himalrandia lichiangensis (Rubiaceae), to evaluate the effects of tectonic and climatic processes on this thermophilic plant species from the dry-hot valleys. By sequencing DNA from four plastid non-coding regions (psbM-trnD, trnD-trnT, atpB-rbcL and accD-psaI) and the CAMX1F-CAMX2R region and ITS for 423 individuals from 23 populations, we investigated the genetic diversity, phylogeographical pattern and population dynamics of H. lichiangensis. We found a high degree of differentiation in H. lichiangensis during the middle Miocene (15-13 Myr), possibly triggered by the rapid tectonic uplift event in this period area. accompanied by frequent orogeneses in this period. This hypothesis is also supported by the association between genetic differentiation and altitudinal gradients among populations. The middle reach of the Jinsha River, which harbors the greatest genetic diversity, is most likely to have been a refugia for H. lichiangensis during Quaternary. We also detected a strong barrier effect between the Nanpan River and Jinsha River, suggesting the river system may play a role in geographical isolation between clades on both sides of the barrier. The Maximum Entropy Model (MaxEnt) results showed that future climate warming will lead to the niche expansion in some areas for H. lichiangensis but will also cause a scattered and fragmented distribution. Given the high among-population differentiation and no recent expansion detected in H. lichiangensis, its current phylogeographical pattern is possibly due to a long-term geographical barrier caused by uplifting mountains since the Miocene, as well as Quaternary climate refugia isolated also by high mountains. This study illustrated tectonic and climatic processes may have a continuous effect on plant phylogeography and offers insights into the origin of biodiversity and endemism in the dry-hot valleys of southwestern China.